2004
DOI: 10.1177/0886260504266229
|View full text |Cite
|
Sign up to set email alerts
|

Lay Persons’ Versus Psychologists’ Judgments of Psychologically Aggressive Actions by a Husband and Wife

Abstract: Literature assessing knowledge of and attitudes toward social issues has demonstrated that mental health professionals and lay persons often differ greatly. To add to the normative information in the field of psychological abuse and to determine whether the differences previously found between mental health professionals and lay persons extend to this field, a sample from each group rated psychologically aggressive items by a husband toward his wife. For the 102 items, psychologists were more likely to label t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
(31 reference statements)
3
11
4
Order By: Relevance
“…Similarly, both genders report that females engage in a form of abuse that involves the issue of trust (i.e., checking on details) more than respondents' reports of males ever engaging in this behavior. This finding seems to parallel previous research in which laypersons tended to view monitoring behaviors as a marital right more than a means of controlling one's partner (Follingstad, Helff, Binford, Runge, & White, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, both genders report that females engage in a form of abuse that involves the issue of trust (i.e., checking on details) more than respondents' reports of males ever engaging in this behavior. This finding seems to parallel previous research in which laypersons tended to view monitoring behaviors as a marital right more than a means of controlling one's partner (Follingstad, Helff, Binford, Runge, & White, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…Should we consider the initiator abusive when the other partner is vulnerable or sensitive to conflict, but not consider the initiator abusive if a recipient is not bothered by the behavior? These findings mirror those of a previous study (Follingstad et al, 2004b) in which lay persons-more so than psychologists-tended to deem behaviors to be a greater violation when they had the potential to produce emotional hurt.…”
Section: Psychological Abuse 17supporting
confidence: 85%
“…In addition to the myriad problems inherent in collecting self-report data on sensitive topics, this approach seems to turn a blind eye to the interpersonal nature of psychological interchanges in intimate relationships as well as ignore nuances of and contextual meanings for these types of behaviors. Researchers have already determined that these brief checklist items are not viewed similarly by all clinicians (Follingstad & DeHart, 2000), or by psychologists versus lay persons (Follingstad et al, 2004b). In addition, psychologists do not rate these as constituting similar levels of abuse when the behaviors are enacted by a husband versus a wife (Follingstad et al, 2004a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Follingstad and DeHart (2000) reported that using a sample of psychologists, the frequency and the duration of abuse were more influential in identifying psychological abuse than intentions or the perceptions of harm by the victim. However, Follingstad, Helff, Binford, Runge, and White (2004) subsequently found that lay persons were more reliant on information regarding the perpetrator's intentions than the frequency of the behavior. Further research is required to examine whether an intent distinguishes the perceptions of normal relational disputes and accidental harm from IPV and how this factor interacts with both the gender of the perpetrator and participant as well as the frequency of violence.…”
Section: Intent To Cause Harmmentioning
confidence: 95%